THE MINIMAL LANDSCAPE - Ntarara, Evangelia (Design/Arts/Culture, 2023)
The article develops an ecological approach (of space or landscape) that is framed by photographic works that capture the dark background of the night sky. The works presented display significant visual information about the environment and belong to heterogeneous photographic genres such as astrophotography or artistic documentary. The various photographic techniques presented through the works visualize visible and invisible radiations that prevail in the dark background of space. Taken as a whole, they broaden the perception of space and highlight the modern phenomenon of light pollution and the invasion of new information into space. The ecological approach is also framed by historical data that connect the evolution of photography and the photographic way of recording space with technological progress, the discovery of new places, the creation of metropolises, and especially the course of urban lighting, which is responsible for the majority of light pollution. Human intervention transforming the urban and natural environment has changed spatial experience, and capitalist organization of production has created a traumatic imprint on the environment. The idea that capitalism can provide the solutions that will reverse the burdened state of the ecosystem is not only not confirmed, but spaces seem to be minimized, shrinking, and landscapes alienated and homogenized. Light pollution now prevails across the planet, and in addition to the loss of the experience of darkness and the energy-intensive state, it threatens human health, flora, and fauna of the ecosystem. The homogenization of modern conditions, as recorded photographically, ultimately emerges as a condition that has arisen from the interventionist approach to the environment.